TINJAUAN MAQASHID SYARIAH TERHADAP KONSEP SAKINAH BAGI SUAMI PERANTAU DI DESA LOJI KECAMATAN SIMPENAN KABUPATEN SUKABUMI - Ramadhan, Taufiq; Rochman, Kholilur; Munawar, Sofyan (Program Studi Hukum Keluarga Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
The purpose of this study is to analyse the concept of sakinah for overseas husbands from the perspective of Maqashid Syariah. This research aims to find out the suitability of efforts to maintain household harmony by overseas husbands with the principles and objectives of sharia, as well as to understand the impact of overseas on communication and relationships in the family. The research method used is qualitative with the type of case study research (field research). The results of this study indicate that: The maqashid sharia review of the Sakinah family for the husband of migrants in loji village, simpenan sub-district, sukabumi has implemented their rights and obligations in the 5 elements, namely maintaining religion, soul, mind, offspring, and property. In addition, the concept of building a sakinah family in loji village, simpenan sub-district, sukabumi for migrating couples is that wives are willing to be left by their husbands to migrate out of town but communication must be maintained continuously, either by chatting whatapps, telephone or video call, and husband and wife can maintain trust. The impact of the husband's migration is positive and negative. The positive is that the family economy has improved, while the negative is the loss of the father's role in the family and the rights of children and other wives are also not fulfilled.